Release-modulating mechanism and comparative pharmacokinetics in beagle dogs of bethanechol-loaded oral dosage forms - Jeong, Hyeong Mo; Kim, Hansol; Jang, Taeyeon; Choi, Ayoung; Park, Jun Bom; Park, Chulhun; Lee, Beom Jin (International Journal of Pharmaceutics, 2025)
Bethanechol chloride (BTC), a quaternary ammonium compound used in bladder dysfunction treatment, requires challenges in developing optimal oral dosage forms due to its high water-solubility, short half-life, rapid elimination and four times a day administration. The aim of this study was to develop optimal BTC-loaded oral dosage forms that could provide both rapid onset and sustained therapeutic effects while reducing the frequency of conventional four-times-daily dosing (Mytonin® tablets). Four different BTC-loaded oral dosage forms were designed including gastro-retentive tablet (GRT), controlled-release tablet (CRT), bilayer tablet (BLT), and tablet-in-tablet (TIT). Then, release-modulating mechanism and in vivo pharmacokinetics in beagle dogs were compared. The release profiles of the four BTC-loaded dosage forms varied according to system design and formulation composition. The optimized GRT F-5 showed rapid buoyancy within 15 s and floated for 12 h, while continuously releasing the drug. CRT showed Fickian diffusion release, whereas BLT and TIT exhibited biphasic immediate and sustained release profiles. Polymer swelling behavior was analyzed using the Vergnaud model, where GRT F-5 and CRT showed n values < 0.5, confirming diffusion-controlled polymer hydration mechanism. In the instrumental analysis, the hydrogen bonding formation of BTC with release-modulating polymers, such as hydroxypropyl methylcellulose and polyethylene oxide and loosening of the polymer structure was crucial as the water influx increased. In pharmacokinetic studies in beagle dogs, the area under the plasma concentration–time curve (AUC) by normalizing dose for 48 h for GRT, CRT, BLT, and TIT were 90.2 %, 108.6 %, 83.8 %, and 76.4 %, respectively, compared with that of the reference drug (Mytonin® tablets, immediate release, four times a day). Interestingly, the plasma maximum concentration (Cmax) and AUC)0-12h of GRT F-5 and and Mytonin® tablets for the first 12-h period were much higher compared with that of other BTC-loaded CRT, BLT, and TIT. BTC was absorbed throughout the gastrointestinal tract, but is preferably absorbed in the stomach and upper intestinal sites. However, the GRT F-5 could provide more therapeutic potential for improving patient compliance in bladder dysfunction treatment by achieving both rapid onset and sustained drug release with reduced dosing frequency.
Keywords: Administration, Oral; Animals; Biological Availability; Chemistry, Pharmaceutical; Delayed-Action Preparations; Dogs; Drug Liberation; Female; Half-Life; Male; Solubility; Tablets; Absorption site; Bilayer tablet; Comparative pharmacokinetics; Controlled-release tablet; Dissolution-modulating mechanisms; Gastro-retentive tablet; Oral dosage forms; Quaternary ammonium compounds; Tablet-in-tablet